An agent-based model for simulation of traffic network status: Applied to Hanoi city. (November 2016) - Nguyen, Manh Hung; Ho, Tuong Vinh
In recent times there have been many agent-based simulation models proposed for transportation network simulation. Intuitively, these models are applicable for the transportation simulation of modern cities in developed countries where the transportation network is very well organized: Roads are separated into lanes; most transportation occurs using vehicles; and almost all drivers respect the circulation rule. However, these models are not suitable for developing countries where the transportation network is unorganized . The reasons for this are as follows: (1) there is no lane on the road; (2) most vehicles are motorbikes; and (3) not many drivers respect the circulation rule. This paper introduces an agent-based model for transportation network simulation in which each form of transport is modeled as an agent exhibiting full features of unorganized circulation behavior. The model is designed for a large scale and instead of displaying the circulation for all individual modes of transport, the model displays only the status of the traffic network. The simulation of circulation is therefore considered as a background process. The simulation is launched and the results are obtained before being displayed. This model is applied to the traffic network of Hanoi to analyze the hot or bottle neck points on the transportation network during rush hours in the city.